Deep sternal wound infection after cardiac surgery: a comparison of three different wound infection types and an analysis of antibiotic resistance - Ma, Jia-Gui; An, Jian-Xiong (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: Deep sternal wound infection (DSWI) is a severe complication following cardiac surgery. We compared epidemiology, clinical features, and microbiology of three types of DSWI and examined the antibiotic resistance in DSWI patients. Methods: From 2011 to 2015, 170 adult post-cardiac surgery DSWI patients were recruited for this study and underwent the pectoralis major muscle ap transposition in our department. Results: Of 170 adult patients with DSWI (mean age of 54 years), the majority (99 patients, 58.2%) had type II DSWI. The three types of DSWI patients showed signi cant differences in terms of gender, smoking history, chronic obstructive pulmonary disease (COPD), length of intensive care unit (ICU) stay, and hospitalization cost (P